2018
DOI: 10.1371/journal.pone.0195740
|View full text |Cite
|
Sign up to set email alerts
|

Large scale newborn deafness genetic screening of 142,417 neonates in Wuhan, China

Abstract: Almost one third of the three million people in China suffering severe deafness are children, and 50% of these cases are believed to have genetic components to their etiology. Newborn hearing genetic screening can complement Universal Neonatal Hearing Screening for the diagnosis of congenital hearing loss as well as identifying children at risk for late-onset and progressive hearing impairment. The aim of this joint academic and Ministry of Health project was to prototype a cost effective newborn genetic scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 54 publications
2
23
0
Order By: Relevance
“…51–53 The largest study to date of 142,417 Chinese newborns identified a carrier rate of 3.01% for the four most common genetic causes of deafness but did not include audiologic data to determine how genetic screening could augment physiologic screening. 54 This variability in detection rates might reflect differences in sample sizes, variants screened, and screening methodologies; however, the data do indicate that even limited genetic screening can identify newborns who otherwise would have been missed by physiologic screening alone.…”
Section: Incorporating Genetic Screening Into the Nbhsmentioning
confidence: 96%
“…51–53 The largest study to date of 142,417 Chinese newborns identified a carrier rate of 3.01% for the four most common genetic causes of deafness but did not include audiologic data to determine how genetic screening could augment physiologic screening. 54 This variability in detection rates might reflect differences in sample sizes, variants screened, and screening methodologies; however, the data do indicate that even limited genetic screening can identify newborns who otherwise would have been missed by physiologic screening alone.…”
Section: Incorporating Genetic Screening Into the Nbhsmentioning
confidence: 96%
“…Two genes MMACHC and MUT were screened and identified 11 patients with MMACHC and three with MUT gene mutations, thus estimated total incidence of 1:16,883. 20 Similarly, a large scale newborn screening of 142,417 neonates for common genetic deafness disorder revealed total 4289 (3.01%) newborns carrying at least one allele of the disease-causing gene GJB2 c.235delC, SLC26A4 c.919-2A>G and mitochondrial variants m.1555A>G and m.1494C>T. 21 Estimating the carrier frequency from Saudi population, Abouelhoda et al, 21 observed highest carrier frequency of 0.0218 for CYP1B1 gene mutation (c.1103G>A: p.Arg368His), which causes congenital glaucoma and considered as a founder mutation. Similarly, carrier frequency for variant (c.20A>T: p.Glu7Val) in the HBB gene was observed as 0.0228, which causes thalassemia and sickle cell anemia.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, large scale genetic screenings of HL have been performed, [12,13] however, most of these studies only focused on several most common variants (such as c.235delC of GJB2 , c.919-2A>G of SLC26A4 , and mitochondrial m.1555A>G). Accurate and timely detection of other disease-causing mutations and related genes play a pivotal role in patients with HL.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Hao et al screened 142,417 neonates from Wuhan using 4 recurrent deafness mutations, including 1 mutation in gene GJB2 (c.235delC), 1 mutation in gene SLC26A4 (c.919-2A>G), and 2 mitochondrial mutations (m.1494C>T and m.1555A>G). [13] However, genetic hearing screening using a small number of recurrent mutations is insufficient. To date, there are more than a 100 genes described to be related to HL.…”
Section: Introductionmentioning
confidence: 99%